The etiology of cleft palate: a 50-year search for mechanistic and molecular understanding - Abbott, Barbara D. (Birth defects research. Part B. Developmental and reproductive toxicology, 2010)
Dates of special, historical significance, such as the 50th anniversary of the founding of the Teratology Society, prompt a desire to pause and look back and contemplate where we began, how far we have come, and consider the future for our scientific endeavors. The study of the etiology of cleft palate extends many years into the past and was a subject of interest to many of the founding members of the Teratology Society. This research area was intensively pursued and spawned a vast portfolio of published research. This article will look back at the state of the science around the time of the founding of the Teratology Society, in the 1950s and 1960s, and track the emergence and pursuit of an interest in an etiology for cleft palate involving failure of palatal fusion. Studies of medial epithelial cell fate and induction of cleft palate by interference with adhesion or fusion span the period from the 1960s to the present time. Teratology Society members have been and continue to be key players in cleft palate research. In this retrospective article, seminal research published by Teratology Society members will serve as a platform to launch the discussion of the emergence of our current understanding of medial epithelial cell differentiation and fate and the potential for these processes to be targets of teratogenic action. Birth Defects Res (Part B) 89:266–274, 2010. Published 2010 Wiley‐Liss, Inc.